Transparency of monetary policy : theory and practice - Petra Maria Geraats (Center for Economic Studies and ifo Institute (CESifo), 2005)
Transparency has become one of the main features of monetary policymaking during the last decade. This paper establishes some stylized facts. In addition, it provides a systematic overview of the practice of monetary policy transparency around the world. It shows much diversity in information disclosure, even for central banks with the same monetary policy framework, including inflation targeting. Nevertheless, the paper finds significant differences in transparency across monetary policy frameworks. The empirical findings are explained using key insights distilled from the theoretical literature. Thus, this paper aims to bridge the gap between the theory and practice of monetary policy transparency.
Keywords: E58; D82; 330; transparency; monetary policy; central bank communication; Geldpolitik; Zentralbank; Kommunikation; Staatliche Information; Welt